Estadios parasitarios presentes en hortalizas comercializadas en Chiclayo, Perú - Morante Chavarry, César (2024)
The risk of infection by parasitic agents in contaminated vegetables is greater when the characteristics of the sale stalls in markets and the hygiene of street vendors is poor. This study aimed to determine the prevalence of parasitic stages and identify the genera/species found in vegetables sold in the main markets of the city of Chiclayo, Peru. In total, 600 vegetable samples were analysed, 75 for each species: lettuce, green onion, celery, radish, cabbage, coriander, parsley and spinach. Using wet mounting, it was determined that 51% (95%CI 47-55) of the samples contained parasitic stages. Entamoeba spp, Giardia spp, Balantidium coli, Taenia spp, Enterobius vermicularis, Ascaris spp, Trichuris spp, Toxocara spp, and Hymenolepis nana were identified. The proportion of protozoan cysts/oocysts was higher than helminth eggs. Lettuce and green onion were the vegetables with the highest presence of parasitic stages. It is concluded that the vegetables sold in the main districts of Chiclayo are highly contaminated with parasitic stages.